Globalization and Language in the Spanish Speaking World
XIII, 270 p.
Keywords: This volume considers the spread of Spanish today and particularly its role in the processes of globalization. Spanish is frequently dominant in contact with other languages. But how contested is its hegemony and how far does it threaten other languages? How are these other minoritized languages faring in a world of few strong, global languages?